Micro finite element analysis of dental implants under different loading conditions. (1st May 2018) - Marcián, Petr; Wolff, Jan; Horáčková, Ladislava; Kaiser, Jozef; Zikmund, Tomáš; Borák, Libor
Abstract: Osseointegration is paramount for the longevity of dental implants and is significantly influenced by biomechanical stimuli. The aim of the present study was to assess the micro-strain and displacement induced by loaded dental implants at different stages of osseointegration using finite element analysis (FEA). Computational models of two mandible segments with different trabecular densities were constructed using microCT data. Three different implant loading directions and two osseointegration stages were considered in the stress-strain analysis of the bone-implant assembly. The bony segments were analyzed using two approaches. The first approach was based on Mechanostat strain intervals and the second approach was based on tensile/compression yield strains. The results of this study revealed that bone surrounding dental implants is critically strained in cases when only a partial osseointegration is present and when an implant is loaded by buccolingual forces. In such cases, implants also encounter high stresses. Displacements of partially-osseointegrated implant are significantly larger than those of fully-osseointegrated implants. It can be concluded that the partial osseointegration is a potential risk in terms of implant longevity. Highlights: Using micro-FEA, bone-implant interaction was assessed for different stages of osseointegration and for various loadings. Trabecular structure of human mandible was analyzed using Mechanostat hypothesis and compression/tension limits of bone. Mechanical stress in dental implant might exceed yield limit in case of partial osseointegration. Partial osseointegration is a potential risk in terms of implant reliability.